Encyclopedia of Cognitive Science 2006
DOI: 10.1002/0470018860.s00567
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Relativity

Abstract: Languages differ dramatically from one another in terms of how they describe the world. Does having different ways of describing the world lead speakers of different languages also to have different ways of thinking about the world?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 14 publications
4
58
1
4
Order By: Relevance
“…For example, cross-linguistic differences in the expression of categories or concepts can lead to corresponding differences in performance on 'perceptual' tasks such as visual search or same-different judgment tasks. These effects are found across a wide range of domains (e.g., Boroditsky, 2003). There are also multiple studies showing that learning novel categories can lead to changes in performance on these types of tasks (e.g., Drivonikou, Clifford, Franklin, & Davies, 2011;Goldstone, 1994;Notman, Sowden, & Özgen, 2005;Özgen & Davies, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…For example, cross-linguistic differences in the expression of categories or concepts can lead to corresponding differences in performance on 'perceptual' tasks such as visual search or same-different judgment tasks. These effects are found across a wide range of domains (e.g., Boroditsky, 2003). There are also multiple studies showing that learning novel categories can lead to changes in performance on these types of tasks (e.g., Drivonikou, Clifford, Franklin, & Davies, 2011;Goldstone, 1994;Notman, Sowden, & Özgen, 2005;Özgen & Davies, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…That is, people talk about time by using spatial expressions, which also suggest that locative relations are more basic and provide structural templates (Evans 2003, Boroditsky 2003, Lyons 1977. Sign languages offer clear cases to observe that spatial relations are encoded in signing space (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the experimental studies reported here, we tested two competing theoretical hypotheses about the relation between evidentiality and source monitoring. According to one hypothesis, evidentiality markers could enhance memory for sources in Turkish compared to English speakers by allowing people to recall or reconstruct source information based on the systematic differentiation of those sources at the linguistic level (Boroditsky, 2003;Imai & Gentner, 1997;Levinson, 2003;Lucy, 1992;Whorf, 1956). According to another hypothesis, evidential language might not produce deep attention-driven reorganization of source-monitoring processes (Gleitman & Papafragou, 2005Landau et al, 2010;Papafragou et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…2 Several commentators have proposed that language has a deep and lasting effect on cognitive processes (Boroditsky, 2003;Imai & Gentner, 1997;Levinson, 2003;Lucy, 1992;see Whorf, 1956 for an early statement of this position). On this view, habitual differences in linguistic framing of events across language communities may lead to stable differences in how members of these communities remember and reason about events even when they are not explicitly using language (i.e., speaking or comprehending speech).…”
Section: Linguistic Evidentiality and Source Monitoringmentioning
confidence: 99%